Extraction of caffeine and gallic acid from coffee by electrokinetic methods coupled with a hollow‐fiber membrane. Issue 6 (7th August 2017) - Khajeh, Mostafa; Fard, Sahar; Bohlooli, Mousa; Ghaffari‐Moghaddam, Mansour; Khatibi, Ali
Abstract: In this study the hollow fiber membrane coupled with electrokinetics was used, for the first time, for extraction and determination of caffeine and gallic acid from coffee prior to high performance liquid chromatography with photodiode array detection. Gallic acid (as an acid) and caffeine (as a base) were extracted from coffee at pH 5. In this work, several variables including applied voltage, coffee pH, acceptor phase pH, and extraction time were investigated. Our results showed that the extraction efficiency was increased when the applied voltage and extraction time were increased. The optimum conditions were pH 5 for the coffee, applied voltage of 20 V, and extraction time of 5 h. Gallic acid as an acid and caffeine as a base migrated to anode and cathode, respectively. Under the optimum conditions, gallic acid and caffeine were extracted with extraction efficiency of 21.3 and 23.4%, respectively. The intra‐day and inter‐day precisions (%) were found to be 7.6 and 4.8%, respectively. Therefore, this set‐up for electrokinetics was potentially considered as a selective and simple preparation method for simultaneous extraction and analysis of basic and acid compounds in various matrices. Practical applications: This study would benefit for extraction and separation of caffeine and gallic acid from coffee and other naturel samples. In this procedure, the new set‐up for EKE based on two hollow fibers were employed for simultaneous removal of basic and acidic compounds. The EKE is used for extraction of organic compounds from food/soils with low permeability. The practical applications of this procedure have become extensive in a variety of fields, including electrokinetic waste remediation, biomaterials, radionuclides, and organic materials.